2009
DOI: 10.1073/pnas.0910310106
|View full text |Cite
|
Sign up to set email alerts
|

Reexposure of cord blood to noninherited maternal HLA antigens improves transplant outcome in hematological malignancies

Abstract: Cord blood (CB) hematopoietic stem cell transplantation can be successful even if donor and recipient are not fully matched for human leukocyte antigens (HLA). This may result from toleranceinducing events during pregnancy but to date this concept has not been tested in CB transplantation. Hence we analyzed the impact of fetal exposure to noninherited maternal antigens (NIMA) of the HLA-A, -B antigens, or -DRB1 alleles on the outcome of CB transplants. The 1,121 patients studied were transplanted for hematolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(111 citation statements)
references
References 30 publications
4
103
0
4
Order By: Relevance
“…In patients with haematological malignancies, NIMA-matched grafts were associated with a lower transplant-related mortality and improved engraftment, leading to reduced overall mortality compared with HLA mismatched, non-NIMA-matched CBT. 7 Improved outcomes were observed for both single mismatches with one NIMA match (5/6+1 NIMA) and two mismatches with one NIMA match (4/6+1 NIMA). A subsequent multicentre study confirmed the lower transplant-related mortality and improved survival associated with NIMA matching.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In patients with haematological malignancies, NIMA-matched grafts were associated with a lower transplant-related mortality and improved engraftment, leading to reduced overall mortality compared with HLA mismatched, non-NIMA-matched CBT. 7 Improved outcomes were observed for both single mismatches with one NIMA match (5/6+1 NIMA) and two mismatches with one NIMA match (4/6+1 NIMA). A subsequent multicentre study confirmed the lower transplant-related mortality and improved survival associated with NIMA matching.…”
Section: Introductionmentioning
confidence: 88%
“…A median of four NIMA-matched donors was available by searching the BMDW registry, thus creating a pool of potential donors, with weighting of other variables such as TNC dose and CD34 + cell content, to be considered in graft selection. Furthermore, in patients with haematological myeloid malignancies, a reduced relapse frequency after NIMA-matched CBT has been reported, 7 suggesting there may also be disease-specific cases where a NIMA match is preferred over an inherited 6/6 HLA match but this may also be dependent on whether the NIMA is a class I or class II HLA.…”
Section: Discussionmentioning
confidence: 99%
“…8 In a recent publication, evidence was presented that, in cord blood transplantation, taking the inherited maternal Ag into account would improve the take of the graft, and transplant outcome would have, if these findings are confirmed prospectively, the advantage of a large number of suitable phenotypes. 7 The epoch in which we were only looking for an adult HLA-matched donor is definitively over. The future challenge is to learn from prospective and retrospective studies how to select the optimal HLA-mismatched donor if an HLA-identical donor is not available.…”
Section: New Developments In Donor Selectionmentioning
confidence: 99%
“…4,5 If an unrelated donor is the only option, putative immunity of the mother against the inherited paternal Ags of her child and the immune response (that is, tolerance and/or immunity) of the child against noninherited maternal Ags should be taken into account. 6,7 It is clear that, apart from the HLA-identical sibling, there does not exist one 'second best stem cell donor.' For 60-70% of patients of Northwest European descent, this will be a 10 out of 10 allele-matched unrelated donor.…”
Section: New Developments In Donor Selectionmentioning
confidence: 99%
“…They include refined techniques for cord blood selection, such as selecting cord blood units that are matched for the noninherited maternal allele; patients receiving these grafts have a similar survival to those patients receiving fully matched UCB units. 15,16 Investigators from Italy have pioneered the injection of cord blood directly into the BM. 17 Finally, several centers are using expansion techniques in an attempt to improve engraftment and immune recovery.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%